The Functions of the CHaracers’names In Iraqi novel ( A study of selected samples) GHANIM HAMEED - GHANIM HAMEED ABBOODI ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The research article studies the importance of the fictional character, as the active element in the novel’s construction, and expressing the writer’s thought. The character represents in the novel a social sample through which society, its political transformations, and its social and cultural concerns can be expressed.The study examines the relationship between character name and the novel’s title ; The difference between the name and the title, and how the name and title come together in the fictional characters.The research article also studies the functions performed by the names of characters in the Iraqi novel. After extrapolating selected models, many functions were revealed in the fiction work, namely:( The functions of moral qualities-a socio-religious function - an ideological cultural function - a historical function - a heritage function - a temporal and spatial function - an interpretive function - a mythological function - a paradoxical function). The study examines selected models of Iraqi novels in which the functions of the names of the characters and their connotations are examined within the fiction work.